Metabolic and renal predictors of coronary artery calcification: the independent role of the uric acid/estimated glomerular filtration rate (UA/eGFR) ratio and Castelli indices - Zarina Babić Jušić; Mirza Babić; Sabina Prevljak; Emir Bećirović; Fuad Zukić; Minela Bećirović; Amir Bećirović (Medicinski glasnik, 2026)
ABSTRACT Aim: To examine the association between metabolic parameters and novel cardiometabolic indices with the coronary artery calcium score (CACS). Methods: This retrospective cross-sectional study included 130 patients who underwent coronary computed tomography angiography (CCTA) at the Radiology Clinic of the Clinical Centre of the University of Sarajevo between January and June 2024. Patients were classified into two groups: those with CACS ?100 and those with CACS >100. Platelet count, mean platelet volume (MPV), estimated glomerular filtration rate (eGFR), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglycerides (TG), uric acid (UA), and novel cardiometabolic indices, including Castelli risk index I and II (CRI-I and CRI-II), non-high-density lipoprotein cholesterol (non-HDL-C), were compared between the groups. Results: Patients with CACS >100 had significantly higher MPV, TC, LDL-C, UA, non-HDL-C, CRI-I, CRI-II, and the UA/eGFR ratio. Older age, increased platelet activity, dyslipidemia, hyperuricemia, and the higher UA/eGFR ratio correlated positively with CACS, whereas eGFR correlated negatively. In multivariate regression analysis, the UA/eGFR ratio emerged as an independent predictor of higher CACS (OR = 2.37; 95% CI 1.18-4.78; p=0.017). Conclusion: Elevated UA levels and adverse cardiometabolic indices are associated with greater coronary artery calcification. The UA/eGFR ratio independently predicts higher CACS, highlighting its potential prognostic value. Keywords: coronary angiography, glomerular filtration rate, uric acid, vascular calcification
Keywords: coronary angiography; glomerular filtration rate; uric acid; vascular calcification